Environmental Degradation, ICT and Inclusive Development in Sub-Saharan Africa - Simplice Asongu; Sara Le Roux; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2017)
This study examines how information and communication technology (ICT) complements carbon dioxide (CO2) emissions to influence inclusive human development in forty-four Sub-Saharan African countries for the period 2000-2012. ICT is measured with internet penetration and mobile phone penetration. The empirical evidence is based on Generalised Method of Moments. The findings broadly show that ICT can be employed to dampen the potentially negative effect of environmental pollution on human development. We establish that: (i) ICT complements CO2 emissions from liquid fuel consumption to increase inclusive development; (ii) ICT interacts with CO2 intensity to negatively affect inclusive human development and (iii) the net effect on inclusive human development is positive from the complementarity between mobile phones and CO2 emissions per capita. Conversely, we also establish evidence of net negative effects. Fortunately, the corresponding ICT thresholds at which these net negative effects can be completely dampened are within policy range, notably: 50 (per 100 people) mobile phone penetration for CO2 emissions from liquid fuel consumption and CO2 intensity. Theoretical and policy implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; ICT; Economic development; Africa